Consciousness, Functional Networks and Delirium Screening - Eeles, Eamonn; Burianova, Hana; Pandy, Shaun; Pinsker, Donna (Current Aging Science, 2017)
Background: Consciousness, the medium of sentient thought, requires integrity of functional networks and their connectivity. In health, they function as a co-operative but mutually exclusive paradigm of introspection versus external awareness subserved via the Default Mode Network and Task Positive State, respectively. Higher thinking in the conscious state is then segregated according to need. There is research evidence to suggest that functional networks may be impacted in disorders of consciousness and conceptual support for a mechanistic role in delirium. This potentially central aspect of delirium manifestation is relatively unexplored. Objective: This article describes the role of disrupted functional networks in delirium. How this relates to current understanding of delirium neurobiology and the ramifications for clinical diagnosis is discussed. Method: A review of the role of functional networks, particularly DMN and TPN, has been undertaken with respect to health and delirium. An exploration of how symptoms of delirium may be related to functional network aberrancy has been undertaken. Implications for research and clinical practice in delirium have been presented. Results: In delirium, a disturbance of consciousness, the DMN is pathologically co-activated and functional cortical connectivity is compromised. The clinical correlate is of an experiential singularity where internal and external drivers become indistinguishable, reality and delusion merge and the notion of self is effaced. Our group propose that functional network disruption in conjunction with cortical disconnectivity is central to the mechanism of delirium. Clinical tools may exploit the neurobiology of delirium to improve its diagnosis and an example of such a simple screening instrument (SQeeC) is provided. Conclusion: Functional networks are critically disrupted in delirium and may be central to clinical features. A better understanding of the neurobiology of delirium will generate research opportunities with potential for therapeutic gains in detection, diagnosis, and management.
Keywords: neurobiology